A circular ferrofluid driven microchip for rapid polymerase chain reaction - Sun, Yi (2012)
In the past few years, much attention has been paid to the development of miniaturized polymerase chain reaction (PCR) devices. After a continuous flow (CF) PCR chip was introduced, several CFPCR systems employing various pumping mechanisms were reported. However, the use of pumps increases cost and imposes a high requirement on microchip bonding integrity due to the application of high pressure. Other significant limitations of CFPCR devices include the large footprint of the microchip and the fixed cycle number which is dictated by the channel layout. In this paper, we present a novel circular close-loop ferrofluid driven microchip for rapid PCR. A small ferrofluid plug, containing sub-domain magnetic particles in a liquid carrier, is driven by an external magnet along the circular microchannel, which in turn propels the PCR mixture through three temperature zones. Amplification of a 500 bp lambda DNA fragment has been demonstrated on the polymethyl methacrylate (PMMA) PCR microchip fabricated by CO2 laser ablation and bonded by a low pressure, high temperature technique. Successful PCR was achieved in less than 4 min. Effects of cycle number and cycle time on PCR products were investigated. Using a magnet as the actuator eliminates the need for expensive pumps and provides advantages of low cost, small power consumption, low requirement on bonding strength and flexible number of PCR cycles. Furthermore, the microchip has a much simpler design and smaller footprint compared to the rectangular serpentine CFPCR devices. To demonstrate its application in forensics, a 16-loci short tandem repeat (STR) sample was successfully amplified using the PCR microchip